LANGUAGE PLAY: ONE WAY OF READING J.K. ROWLING’S HARRY POTTER - Tanto, Trisnowati; Tanusy, Jeanyfer (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2023)
J.K. Rowling and her Harry Potter series, published from 1997 to 2007, have been globally acclaimed as one of the most popular novels with the most varied target readers. A lot of reviews have been made and by far, they focused more on the literary aspects. This research offers a different way of reading Harry Potter novels since it will focus more on language play as Rowling’s style of writing, which is believed to contribute to the comprehension of the literary elements. Language play is a means of foregrounding – linguistic forms that stand out in a text. The research is done to find out the language play forms contained in Harry Potter and the Philosopher’s Stone and how these forms support the understanding of the literary elements. The research employs the descriptive qualitative method; various linguistic forms of language play are taken as the data, which are then investigated further in terms of the types of linguistic features. Afterward, these are connected with the literal and contextual meanings so as to find out how they support the literary elements. The findings show that besides being entertaining, the language play helps support reader’s imagination as well as supporting the characterization and plot. The research also shows that language play deserves considerable appreciation since creating as well as understanding it needs a high language skill from both the author and readers, especially when it is intended not only to be entertaining but to support the literary elements.